Clinical significance of limited and extended pelvic lymph node dissection during robot‐assisted radical prostatectomy for patients with localized prostate cancer: A retrospective, propensity score matching analysis. (28th October 2022) - Hori, Shunta; Nakai, Yasushi; Tachibana, Akira; Omori, Chihiro; Nishimura, Nobutaka; Inoue, Kuniaki; Tomizawa, Mitsuru; Shimizu, Takuto; Morizawa, Yosuke; Gotoh, Daisuke; Miyake, Makito; Torimoto, Kazumasa; et al.
Abstract: Objectives: We investigated the diagnostic and therapeutic benefits of limited or extended pelvic lymph node dissection during a robot‐assisted radical prostatectomy for localized prostate cancer. Methods: Diagnostic and therapeutic benefits were assessed according to the rates of pN1 and biochemical recurrence, respectively. The primary outcome was the biochemical recurrence‐free rate, and secondary outcomes included the diagnostic and therapeutic benefits of pelvic lymph node dissection. Results: A total of 534 patients were analyzed. Out of the 534 patients, 207 (38.8%) received limited pelvic lymph node dissection while 134 (25.1%) received extended dissection. There were 297 patients with a Briganti index ≥5%. Extended dissections yielded significantly more resected lymph nodes ( p  < 0.0001), and 72.2% of cases of pN1 were located outside the obturator. The incidence rate of pN1 was 6.1%, and performance of extended lymph node dissection was an independent predictor for pN1 (odds ratio 9.0, 95% confidence interval 2.5–33.1). The rate of biochemical recurrence was 14.9%, and Cox proportional hazards regression analysis of the propensity score matched population revealed that patients with high or very‐high risk tended to benefit from limited lymph node dissection (hazard ratio 8.4, 95% confidence interval 0.8–82.3) while the therapeutic benefit of extended dissection was unclear by comparison. Conclusions: Extended pelvic lymph node dissection significantly improves diagnostic accuracy; however, the therapeutic benefit of pelvic lymph node dissection was not observed in this study.